2020
DOI: 10.1088/1742-6596/1567/2/022041
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of guided inquiry learning based on contextual to improve chemistry literacy ability of senior high school students

Abstract: This research aims to determine the effectiveness guided inquiry learning based of contextual to improve chemistry literacy ability of students. This is an experimental research with pretest-posttest control group design and cluster random sampling as sampling techniques. The samples of this research are two different classes of X MIPA. The ability of chemistry literacy is tested using chemistry literacy test and questionnaire. Data analysis uses T-test, N-gain, classical learning pass, and questionnaire data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…From this (Table 2), we can conclude that three study articles [26,30,34] utilized the independent t-test as their data analysis method. The independent t-test was employed in these studies to compare the means of two separate groups.…”
Section: Data Analysis Methods Adopted In Icb Studiesmentioning
confidence: 94%
See 1 more Smart Citation
“…From this (Table 2), we can conclude that three study articles [26,30,34] utilized the independent t-test as their data analysis method. The independent t-test was employed in these studies to compare the means of two separate groups.…”
Section: Data Analysis Methods Adopted In Icb Studiesmentioning
confidence: 94%
“…In the data analysis section of reviewing, Table 2 below shows an overview of the types and number of analysis methods adopted by the study articles. Among the study articles, three article [26,30,34] utilized the independent t-test as their data analysis method. Additionally, three study articles [25,27,33] used the oneway t-test.…”
Section: Data Analysis Methods Adopted In Icb Studiesmentioning
confidence: 99%
“…Research samples were treated in experimental and conventional groups in control classes (El Islami, et al, 2019). The development of learners' teaching materials through several stages consists of the validation of expert assessment, validation of materials, and assessment of teacher practicality (Wardani and Anggraeni, 2020). Data collection is done using questionnaires and tests.…”
Section: Methodsmentioning
confidence: 99%
“…SCIENCE teachers argue that this teaching material is very suitable for schools located in coastal areas. Learners can observe directly in the environment and add insight and literacy skills (Burt, et al, 2019;Falloon, 2019;Wardani and Anggraeni, 2020). Based on the teacher validation assessment, all four aspects have a very good score on the category (Table 2 Aspects of material content get three responses: quite, interesting, and very interesting, with consecutive percentages of 4.51%, 35.66%, and 55.32%.…”
Section: Test Of the Feasibility Of Teaching Materialsmentioning
confidence: 99%
“…According to research conducted by Ibnusaputra et al (2023), the application of the guided inquiry learning model with a scientific approach has proven to be very effective in improving students understanding of concepts and critical thinking abilities. The application of the guided inquiry model in education can be improved by incorporating contextual learning, because it functions as a basic framework for fostering scientific thinking and improving students cognitive abilities at a higher level (Wardani & Anggraeni, 2020). According to the findings of Ramandha et al (2018), the application of the guided inquiry learning approach has shown its efficacy in facilitating students understanding of real ideas and encouraging the development of advanced cognitive processes.…”
Section: Analysis Of the Effective Contribution Of The Guided Inquiry...mentioning
confidence: 99%